AFTER THREE-YEAR IMMERSION IN THE AUSTRALIAN MAINSTREAM CLASSROOM: TOWARDS MORE ADVANCED ESL LITERACY LEARNING DEVELOPMENT - Cahyono, Bambang Yudi (k@ta: A Biannual Publication on the Study of Language and Literature, 2006)
This article is one of two studies about literacy learning of Aida, an Indonesian young English language learner who was mainstreamed in an Australian primary school in Melbourne. It described the development of her more advanced literacy learning. This article suggests that a learner’s literacy learning of ESL in the mainstream classroom can be facilitated if there are a number of contributing factors, especially those related to literacy learning policies, learning environment, and teachers’ role.